2006
DOI: 10.1242/jcs.02889
|View full text |Cite
|
Sign up to set email alerts
|

TRAF6 activation of PI 3-kinase-dependent cytoskeletal changes is cooperative with Ras and is mediated by an interaction with cytoplasmic Src

Abstract: Interleukin 1 (IL-1) has been implicated in the reorganization of the actin cytoskeleton. An expression vector encoding a PKB/Akt pleckstrin-homology domain fused to a fluorescent protein was used to detect phosphoinositide 3-kinase (PI 3-kinase) products. It was observed that PI 3-kinase was activated either by treatment with IL-1 or by expression of either TRAF6, Src, MyD88 or dominant-positive PI 3-kinase, and resulted in the formation of long filopodia-like cellular protrusions that appeared to branch at m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
50
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 88 publications
4
50
0
Order By: Relevance
“…In colon cancer cells harboring this variant IL-6 may be particularly effective in advancing the adenoma/ carcinoma sequence. Interestingly, a dominant-negative mutant of c-Jun exhibited a significant antitumor effect in colon cancer demonstrating the possibility of AP-1-based gene therapy as a novel treatment of colorectal cancer (77)(78)(79)(80). Understanding the regulation of NFB and AP-1 and their cross-talk in the regulation of their target genes such as IL-6 may lead to the development of novel therapeutics for the control of inflammatory diseases of the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…In colon cancer cells harboring this variant IL-6 may be particularly effective in advancing the adenoma/ carcinoma sequence. Interestingly, a dominant-negative mutant of c-Jun exhibited a significant antitumor effect in colon cancer demonstrating the possibility of AP-1-based gene therapy as a novel treatment of colorectal cancer (77)(78)(79)(80). Understanding the regulation of NFB and AP-1 and their cross-talk in the regulation of their target genes such as IL-6 may lead to the development of novel therapeutics for the control of inflammatory diseases of the mucosa.…”
Section: Discussionmentioning
confidence: 99%
“…Although a TRAF6 binding protein can disrupt the association of TRAF6 with CD40 and block downstream signaling, it does not interfere with Src activation, placing Src upstream of TRAF6. Src has been shown to interact directly with TRAF6 in overexpression studies (130,133), but this has not been observed in primary macrophages. SFKs have also been implicated in cell survival pathways downstream of TNF family receptors such as receptor activator of NF kappa B (RANK) in osteoclasts; expression of a truncated Src that lacks the kinase domain in osteoclasts of src −/− mice reduces Akt activation, decreases osteoclast survival and exacerbates the osteopetrotic phenotype of src −/− mice (159).…”
Section: Other Macrophage Receptorsmentioning
confidence: 97%
“…Surprisingly, tyrosine phosphorylation resulting from CpG stimulation of macrophages occurs in the absence of either TLR9 or MyD88 implying that SFKs are involved in a distinct pathway that appears to be important for actin cytoskeletal rearrangements (112). This pathway involves PI3K and Akt, and is required for downstream activation of NF kappa B. Tyrosine phosphorylation of MAPKs in response to LPS is lost in macrophages lacking TLR4, but is only delayed in MyD88-deficient macrophages (128) (130,132,133). Src has also been shown to associate with IKK when overexpressed in HEK293 cells (134).…”
Section: Author Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations